Case report: Generalized lymphatic anomaly of multiple abdominal organs in a young dog - Park, So-Hyeon; Lee, Jung-Ha; Salas, Elisa N.; Kim, Myeongsu; Han, Jae-ik; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2023)
A 9-month-old, female Pomeranian dog presented with vomiting and lethargy. Ultrasonography revealed multilobulated anechoic round shape structures at the ovarian and uterine locations. Through computed tomography scan, an extensive non-contrast multilobulated fluid-filled mass suspected of originating from the walls of the ovary, uterus, urinary bladder and rectum was observed. Ovariohysterectomy and urinary bladder biopsy were performed. Histopathological examination revealed numerous cystic lesions lined by plump cuboidal cells believed to be of epithelial origin. Immunohistochemical staining showed that the cyst-like lesions lining cells were strongly positive for lymphatic vessel endothelial hyaluronan receptor 1. Based on these results, lesions were identified as generalized lymphatic anomaly (GLA), in which lymphangiomas develop in multiple organs. After 6 months follow-up, the size of the cysts remaining in the region of the bladder did not undergo much change. GLA should be included in the differential diagnosis when multiple cystic lesions are interspersed in multiple organs.